Spatial and temporal analysis of Rift Valley fever outbreaks in livestock in Uganda: a retrospective study from 2013 to 2022 - Arinaitwe, E.; Atuhaire, D.K.; Hasahya, Emmanuel; Nakanjako, G.K.; Mwebe, R.; Nizeyimana, G.; Afayoa, M.; Mwiine, F.N.; Erume, J. (BioMed Central, 2025)
Background: Rift Valley fever (RVF) is a zoonotic disease caused by the Rift Valley fever virus (RVFV), primarily affecting livestock and transmitted by Aedes mosquitoes. First detected in Kenya in 1930, RVF has since spread across Africa, including Uganda, and to the Arabian Peninsula. Uganda reported its first human cases of RVF in 1968, with sporadic outbreaks continuing since the significant outbreak in 2016, particularly in regions with high livestock populations. Although RVFV was detected in mosquitoes in Uganda as early as 1944, the spatial and temporal distribution of RVF outbreaks has not been thoroughly documented. This study aimed to analyze trends in RVF outbreaks across Uganda from 2013 to 2022 to provide insights for effective control measures. A retrospective study was conducted utilizing archived RVF data from NADDEC, along with rainfall and temperature data from the Uganda Meteorological Centre. Maps were generated using QGIS software to illustrate the spatial distribution of RVF outbreaks. The distribution and trends were analyzed using the R programming language.